2018
DOI: 10.1590/s0004-2803.201800000-88
|View full text |Cite
|
Sign up to set email alerts
|

Irritable Bowel Syndrome, Food Intolerance and Non- Celiac Gluten Sensitivity. A New Clinical Challenge

Abstract: Approximately 80% of irritable bowel syndrome (IBS) patients report that their symptoms are triggered after ingesting one or specific food groups. Gluten, wheat and related proteins (e.g., amylase-trypsin inhibitors, and fermentable oligo-di-mono-saccharides and polyols (FODMAPs) are the most relevant IBS symptom triggers, although the true ‘culprit(s)’ is/are still not well established. The concept of causal relationship between gluten intake and the occurrence of symptoms in the absence of celiac disease and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 89 publications
(232 reference statements)
0
9
0
4
Order By: Relevance
“…Many studies indicated that IBS symptoms are worsened and aggravated by certain foods, such as legumes, milk, spicy food, fried food, and coffee. [ 3 19 43 44 ] Among the study subjects, the majority of the IBS patients reported food restriction due to intolerance. High-fat, high FODMAPs which are fermentable oligosaccharides, disaccharides, monosaccharides, and short chain polysaccharides that are poorly absorbed in small intestine and are prone to absorb water and ferment in the colon, like legumes, cabbage, cauliflower and citrus fruits, milk and milk products were considered by many IBS patients to induce their gastrointestinal symptoms, hence, restricted them from their diet, as compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicated that IBS symptoms are worsened and aggravated by certain foods, such as legumes, milk, spicy food, fried food, and coffee. [ 3 19 43 44 ] Among the study subjects, the majority of the IBS patients reported food restriction due to intolerance. High-fat, high FODMAPs which are fermentable oligosaccharides, disaccharides, monosaccharides, and short chain polysaccharides that are poorly absorbed in small intestine and are prone to absorb water and ferment in the colon, like legumes, cabbage, cauliflower and citrus fruits, milk and milk products were considered by many IBS patients to induce their gastrointestinal symptoms, hence, restricted them from their diet, as compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been reported that approximately 20% to 37% of patients with self-reported NCGS fulfill the criteria to be classified as IBS [ 19 , 31 ]. Due to the lack of sensitive biomarkers for the diagnosis of NCGS and IBS, their differentiation is complicated [ 92 ]. Current studies report that there is a cohort of IBS patients that are sensitive to wheat components, including gluten and FODMAPs [ 42 , 93 ].…”
Section: Diagnosismentioning
confidence: 99%
“…İrritabl bağırsak sendromu (IBS) hastalarının yaklaşık % 80' i, semptomlarının bir veya belirli gıda grubunu tükettikten sonra bulgularının tetiklendiğini bildirmektedir. Gluten, buğday ve ilgili proteinler (örn: amilaz-tripsin inhibitörleri ve fermente edilebilir oligo-di-mono-sakkaritler ve polioller (FODMAP' ler) en önemli IBS semptom tetikleyicisidir, ancak halen tek neden olarak kabul edilmemektedir (Soares, 2018).…”
Section: Bu çAlışmalardan Bazılarıunclassified